Effect OF CO2/N2 dilution on laminar burning velocity of liquid petroleum gas-air mixtures at elevated temperatures. (1st April 2016) - Nair, Aswathy; Velamati, Ratna Kishore; Kumar, Sudarshan
Abstract: The present experimental study reports the effect of CO2 /N2 dilution on laminar burning velocity of premixed LPG (liquid-petroleum-gas)-air mixtures at elevated temperatures using a preheated mesoscale diverging channel technique. The experiments were carried out for a range of equivalence ratios varying from 0.8 < Φ < 1.3 with percentage dilution of the fuel component by volume (β) for CO2 varying from 10% < β < 30% and N2 varying from 10% < β < 40%. A power–law correlation has been obtained for the present experimental data as a function of percentage dilution, mixture temperature and equivalence ratio. It has been observed that an increase in dilution with CO2 /N2 leads to an increase in temperature exponent (α). The increase in temperature exponent due to CO2 dilution is more pronounced as compared to N2 dilution case. A flame structure study has been carried out to understand the effect of mixture temperature and diluent using USC (University of Southern California) Mech II reaction mechanism. Highlights: Effect of CO2 /N2 dilution on burning velocity of LPG-air mixtures investigated. Burning velocity correlation of LPG-CO2 /N2 -air mixtures at high temperatures. Temperature exponent (α) increases with dilution for both N2 and CO2. Flat flames stabilized using a preheated mesoscale diverging channel technique.